Formation of the Granular (Cu, Co) Alloys with Uniform Distribution of Magnetic Granules Using Co Nanoparticle Arrays - V.A. Zlenko; M.G. Demydenko; S.I. Protsenko; A.V. Boyun; A.A. Vozny (Журнал нано- та електронної фізики)
By thermal dispersion of thin metal films produced arrays of fcc-Co nanoparticles (NPs), on amorphous polyimide and Si3N4/Si substrates. The influence of the substrate material, the effective thickness of the initial metal film and heat treatment on the morphology of arrays of NP has been studied. Phase transition processes during formation of structures such as magnetic Co granules in nonmagnetic Cu matrix were investigated. The possibility of obtaining by proposed method of granular (Cu, Co) alloys with a uniform distribution of Co granules in (Cu, Co) solid solution matrix was shown. Magneto-optical properties of obtained structures were investigated.